Effect of extraction method and ripening stage on banana peel pigments - Yan, L.; Fernando, W.; Brennan, M.; Brennan, C.; Jayasena, Vijay; Coorey, Ranil (Wiley-Blackwell Publishing Ltd., 2016)
Carotenoids are one of the most widespread pigments in nature and can be used as health-promoting natural food colorants. Banana peel, which is a by-product of banana processing, contains a range of bioactive compounds including carotenoids. There is no published research on the extraction of food-grade carotenoids from banana peels. This study evaluated the change in the banana peel carotenoid content over its ripening stages and determined the best possible solvent to extract carotenoid for food applications. The solvents permitted under Food Standard Australia New Zealand were used in the study. Ripeness stage 5 contained the highest content of total carotene at 1.86 μg g-1of banana peel. From one gram of banana peel, 0.57 μg of xanthophyll and 0.84 μg of beta-carotene were extracted from ripening stage 5 with a solvent combination of hexane–diethyl ether–acetone and hexane–diethyl ether, respectively.